ANALISIS STRATEGI PEMASARAN KAIN BATIK BESUREK DI KOTA BENGKULU - Handayani, Sri; Hanila, Siti; Nengsih, Mimi Kurnia (JURNAL EKOMBIS REVIEW, 2018)
This study aims to determine the marketing strategy for batik products Besurek in Bengkulu city. And which strategy is best in determining the marketing of batik cloth of Besurek in Bengkulu city. Data collection methods used are literature study method and questionnaire by distributing the list to the respondents. The sample in this study is the assumption of an effective strategy to maximize the strengths and opportunities of small businesses and to minimize weaknesses and threats.Analysis method used in this research is SWOT analysis method (Strength, Weaknesses, Opportunity, Threats). The data obtained from the results of the study will be analyzed strength, weakness, opportunities and amcamannya to the implementation of corporate marketing strategies in order to increase interest buyers batik cloth besurek. To determine the formulation of future marketing strategies, a merger of marketing strategy formulation is linked through the SWOT matrix.